Post-earthquake damage assessments of unreinforced masonry (URM) buildings by shake table test and numerical visualization - Kaya, Ali; Adanur, Suleyman; Bello, Ridwan Adebayo; Genc, Ali Fuat; Okur, Fatih Yesevi; Sunca, Fezayil; Gunaydin, Murat; Altunisik, Ahmet Can; Sevim, Baris (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Masonry structures are one of the structures most affected by earthquakes. In addition, since masonry structures constitute a large part of the building inventory, it is important to determine the dynamic characteristics of these structures. The present study is aimed to evaluate the seismic performance of a half-scale hollow brick unreinforced masonry (URM) building considering different damage states. Shake table test was conducted with seven loading conditions. In order to obtain different damage states, seismic excitations were applied incrementally to structure. After each loading, the damage conditions and the corresponding damage patterns were examined comparatively, and the structure collapsed in the last loading condition. To experimentally observe the damage, the modal parameters for un-damaged and damaged situations of the building were identified by ambient vibration tests performed before and after the seismic loadings. The experimental results obtained were then compared with the analyses made in numerical softwares, and similar results were obtained.
Keywords: Ambient vibration test; Brick; Masonry; Shake table; Earthquake simulation; Blender; MODAL PARAMETER-IDENTIFICATION; NEAR-FAULT; SEISMIC PERFORMANCE; DYNAMIC-RESPONSE; ARCH BRIDGE; TOWERS; VULNERABILITY; BEHAVIOR; FAILURE; MODELS; Engineering; Materials Science